2005
DOI: 10.1177/003335490512000213
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assessment in the Measurement of Public Health Workforce Preparedness for Bioterrorism or other Public Health Disasters

Abstract: In this study, workers' ratings of need for training may reflect an overall interest in training rather than need for training in a particular area. Caution should be exercised in interpretation when generic goals and self-assessment are used to measure need for training. Future assessments of training needs may be more effective if they use objective measures of specific local plans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…Some researchers argue the wording of the question influences the response to it. 16 They further argue that the generic nature of the public health workforce survey questions (the one used in this study) make it difficult to adequately interpret the self-report responses. 16 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some researchers argue the wording of the question influences the response to it. 16 They further argue that the generic nature of the public health workforce survey questions (the one used in this study) make it difficult to adequately interpret the self-report responses. 16 …”
Section: Discussionmentioning
confidence: 98%
“…Or perhaps the responses were based on interest in learning more about a high-profile issue. 16 Another possible explanation may be that the impact of 9/11 and Katrina might have raised the level of urgency to be prepared and meet the public's expectations.…”
Section: Discussionmentioning
confidence: 99%
“…13 Workers were asked to rate their need for training, and the study found that workers could be placed into three groups. The groups differed in their average rating, but within each group, the workers tended to rate the top 10 goals quite similarly.…”
mentioning
confidence: 99%
“…Self-assessment is best used to help individuals analyze their work practices and to promote reflection on performance (Stewart et al, 2000). Individuals using self-assessment should be able to provide summative evaluation of themselves (Kerby et al, 2005) as well as detailed analysis of items that support that summary statement (Eva and Regehr, 2005). Self-assessment can constitute the basis for professional development to further on-the-job learning in collaboration with their nursing peers (Vuorinen et al, 2000).…”
Section: Discussionmentioning
confidence: 99%